2016
DOI: 10.1111/jvec.12204
|View full text |Cite
|
Sign up to set email alerts
|

Hyalomma ticks on northward migrating birds in southern Spain: Implications for the risk of entry of Crimean-Congo haemorrhagic fever virus to Great Britain

Abstract: Crimean-Congo haemorrhagic fever virus (CCHFV) is a zoonotic virus transmitted by Hyalomma ticks, the immature stages of which may be carried by migratory birds. In this study, a total of 12 Hyalomma ticks were recovered from five of 228 migratory birds trapped in Spring, 2012 in southern Spain along the East Atlantic flyway. All collected ticks tested negative for CCHFV. While most birds had zero Hyalomma ticks, two individuals had four and five ticks each and the statistical distribution of Hyalomma tick cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Thus, we tested the ticks for CCHFV and SFGR. While no virus was detected, as was the case in similar surveys (27,44,46), Rickettsia was prevalent in H. rufipes and H. marginatum complex ticks from birds (34.6% and 81.3%, respectively). The sequenced SFGR samples were identified as R. aeschlimannii, a prevalent tick-borne SFGR in the African continent, previously detected in ticks from migratory birds arriving to Europe (49,50).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, we tested the ticks for CCHFV and SFGR. While no virus was detected, as was the case in similar surveys (27,44,46), Rickettsia was prevalent in H. rufipes and H. marginatum complex ticks from birds (34.6% and 81.3%, respectively). The sequenced SFGR samples were identified as R. aeschlimannii, a prevalent tick-borne SFGR in the African continent, previously detected in ticks from migratory birds arriving to Europe (49,50).…”
Section: Discussionmentioning
confidence: 84%
“…These two species were considered part of the Hyalomma (Euhyalomma) marginatum Koch complex until recent years (2), and perhaps the low divergence reflects recent species separation. The RFLP analysis was also useful for the identification of immature stages of Hyalomma ticks, which is a limiting factor for the identification of ticks collected from migratory birds (3,4,27,44). The main species found on migratory birds were H. rufipes and H. marginatum.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported Hyalomma spp. on birds migrating north through Europe (147,148). Further studies have confirmed that such ticks can be infected with zoonotic pathogens (149), such as Crimean-Congo haemorrhagic fever virus.…”
Section: Risks From Exotic Ticksmentioning
confidence: 95%
“…In relation to the training regarding an outbreak scenario, we delivered a research-led workshop (totalling 3 hours, practical element 1 hour long) which consisted of the development of an intervention programme for an outbreak due to the emerging pathogen Category A Crimean-Congo Haemorrhagic Fever virus [10]. We selected this virus as it is threatening countries in Western Europe [11], including the UK [12]. This research-led training was based on a successful novel teaching experience created by our team [13] and was aimed to assure the relevance that biomedical scientists have as key health professionals in any first response team in the aftermath of a biological incident or an outbreak of infection.…”
Section: Changes Undertaken In the "Medical Microbiology" Modulementioning
confidence: 99%